General Picture of Population Distribution in Armenia in the 16th Century on the Example of Several Administrative Units - Malkhasyan, Mikayel (History and Culture, 2021)
In the 16th century, Armenia became the scene of hostilities between the Ottoman Empire and Safavid Iran. The decades-long conflict had a very negative impact on the normal development of Armenia, affecting different directions of socio-economic and cultural spheres. The demographic consequences were especially prominent, as the Armenian population, as a whole demographic system, began to be exposed to external influences that disrupted its normal life. Such influences included the deportation of the population, the forcible collection of children, the system of tax collection based on religious distinctions, the promotion of conversion to Islam, and so on. In such circumstances, the aim of our research is to understand the picture of the distribution of the Armenian population in the administrative units, created by the two foreign powers, through the processes of those negative impacts. In order to achieve this goal, we set a task to extract as much as possible the source database, which is rather narrow for the mentioned period. It also has methodological issues, such as the classification of the population in the Ottoman geographical records not by ethnicity but by religious affiliation.
Keywords: Ottoman Empire; Safavid Iran; Armenia; population distribution; the 16th century; Armenians; separate administrative units